2017
DOI: 10.1002/bmc.3918
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and tissue distribution of coptisine in rats after oral administration by liquid chromatography–mass spectrometry

Abstract: Coptisine, one of the main components isolated from Coptidis rhizoma, has been reported to have many beneficial pharmacological effects including anti-inflammatory, anti-hypercholesterolemia, neuroprotective and cardioprotective properties. However, to date the information related to the in vivo pharmacokinetics (PK) of coptisine is very limited. The purposes of our study are to establish a fast and sensitive quantification method of coptisine using liquid chromatography-mass spectrometry (LC-MS) and evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…This in vivo assay confirms the potential antimalarial activity of coptisine chloride, one of the major bioactive components of Coptis Rhizome [38]. The oral administration of Coptis Rhizome and Orengedokuto, plasma concentration and tissue distribution of coptisine was detected much lower than the berberine and palmatine suggesting that the poor oral absorption and bioavailability of coptisine and fast elimination rate [55,56].…”
Section: Discussionsupporting
confidence: 64%
“…This in vivo assay confirms the potential antimalarial activity of coptisine chloride, one of the major bioactive components of Coptis Rhizome [38]. The oral administration of Coptis Rhizome and Orengedokuto, plasma concentration and tissue distribution of coptisine was detected much lower than the berberine and palmatine suggesting that the poor oral absorption and bioavailability of coptisine and fast elimination rate [55,56].…”
Section: Discussionsupporting
confidence: 64%
“…The content of coptisine is approximately 1/16 of coptisine in Coptis Rhizome [54]. Therefore, our results re ect the contents of these alkaloids in Coptis Rhizome which suggest that the poor oral absorption and bioavailability, and fast elimination rate of coptisine [38,39].…”
Section: Discussionsupporting
confidence: 51%
“…The content of coptisine is approximately 1/16 of coptisine in Coptis Rhizome [54]. Therefore, our results reflect the contents of these alkaloids in Coptis Rhizome which suggest that the poor oral absorption and bioavailability, and fast elimination rate of coptisine [38,39].…”
Section: Discussionmentioning
confidence: 55%
“…The same dose of injection was performed once a day until day 6. The IP route of administration was used since the previous study revealed that coptisine has low oral bioavailability and poorly absorbed through gastrointestinal tracts [38,39] On day 3 (72 hrs post-infection), the parasitemia level were determined by Giemsa-staining of the tail vein blood smears that was characterized by random counting of the number of parasitized erythrocytes on randomly selected fields of the slide under microscopy of 2,000-4,000 erythrocytes when parasitemia was low (≤10 %) or up to 1000 erythrocytes when parasitemia was higher.…”
Section: Assessment Of Antimalarial Activity In Mouse Modelmentioning
confidence: 99%